Workplace training: reinforcing effective job performance / Nur Shafini Mohd Said … [et al.] - Mohd Said, Nur Shafini; Jahya, Nor Syamimi; Mazlan, Nur Amalina; Omar Ali, Siti Rapidah; Mohammed Yusof, Hani Sakina (Universiti Teknologi MARA, Terengganu, 2016)
Training is an “opportunity” given to employees to perform effectively by learning and preparing themselves for any changes in their job. In an era of continuous change and increased environmental uncertainty and complexity, both management and employees understand their limited capacity to deal with future demands made on them. Thus, this paper aims to examine a relationship between three elements of training which are on-the-job and off-the-job training, development, and training benefits with a job performance. This study involves 76 respondents from various departments who work at Pejabat Daerah dan Tanah, in Dungun. A set of questionnaire consists of 30 items was distributed to each selected staff using a convenience technique. Findings of this study reveal that participants who perceived their training as to be adequate and favourable, scored higher on the job performance. Thus, the findings confirm hypothesis 1 that there is a positive relationship between on-the-job and off-the job trainings with a job performance. The findings also confirm hypothesis 2 which there is a positive relationship between development and a job performance. Hypothesis 3 shows that there is a positive relationship between training benefits and a job performance. The results specify that development applies more impact on employees’ job performance rather than on-the-job and off-the-job training and training benefits. Finally, researchers hope that this study would not only give benefits to the management and staff in Pejabat Daerah dan Tanah Dungun but also to other organizations.